Factors Associated With Noncontact Injury in Collegiate Soccer: A 12-Team Prospective Study of NCAA Division I Men's and Women's Soccer. Issue 11 (September 2021) - Curtis, Ryan M.; Huggins, Robert A.; Benjamin, Courteney L.; Sekiguchi, Yasuki; Lepley, Lindsey K.; Huedo-Medina, Tania B.; Casa, Douglas J.
Background: Multiteam, multi-institution prospective studies of both women's and men's sports are essential for collectively investigating injury and primary to the generalization and individualization of injury prevention strategies. Hypothesis: Characteristics of workload, sleep, and contextual factors will be associated with injury risk in collegiate soccer athletes. Study Design: Cohort study; Level of evidence, 2. Methods: Injuries, workload, and sleep characteristics were recorded daily throughout a complete season for 256 athletes from 12 separate National Collegiate Athletic Association Division I men's and women's soccer teams. Workload and contextual factors were assessed via multilevel Poisson regression to capture differences in injury incidence rate ratio (IRR). Paired t test and multilevel logistic regressions were used to assess the relationship between sleep behavior and injury. Results: Collegiate soccer athletes had lower rates of noncontact injury in the in-season (IRR, 0.42) and postseason (IRR, 0.48) compared with preseason, lower rates of injury in training (IRR, 0.64) compared with matches, and higher injury rates with only 1 day of rest in the previous week (IRR, 1.58) compared with >1 day. Injury rates peaked when training occurred 4 days before a match (IRR, 2.24) compared with a match. Injury rate increased exponentially with increases in the number of noncontact injuries incurred throughout the season (IRR, 2.23). Lower chronic loading, higher training monotony, and acute spikes and lulls in workload were associated with higher noncontact injury rates. Alterations in previous week sleep quality were associated with injury, while chronic sleep behavior and acute alterations (<7 days) in sleep behavior were not ( P > .05). Conclusion: Athlete and schedule-specific contextual factors, combined with characteristics of workload and weekly sleep behavior, are significantly associated with injury in collegiate soccer. Multiteam prospective cohort studies involving objective and subjective monitoring allow for the identification of multiple injury risk factors in sports, which can be used to guide injury prevention strategies. Maintaining higher chronic workloads, lowering training monotony, minimizing acute spikes or lulls in workloads, managing workloads during preseason and for athletes with previous injury, integrating more rest and recovery during congested periods, and optimizing sleep quality are all practical considerations for reducing injury risk in collegiate soccer.